Statistical estimation and hypothesis testing on impulse response function - Anastasiia Melnyk; Iryna Rozora (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. This research centers on estimating the impulse response function (IRF) of a time-invariant linear system within a bounded domain. The IRF plays a pivotal role in elucidating the internal dynamics of a system and its reactions to external stimuli, with significant applications in fields such as signal processing, econometrics, and control systems.
Keywords: impulse response function (IRF); linear time-invariant system